EUROREGIONS: CHARACTERISTICS AND PRINCIPLES OF FUNCTIONING (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article examines the principles of functioning and characteristics of euroregions. The forms of implementation of cross-border cooperation can vary from the establishment and development of mutually beneficial contacts between different entities and the conclusion of agreements on cross-border cooperation in certain areas to the creation of international territorial entities. International territorial entities that include border administrative units of neighboring states on the basis of concluded agreements are called euroregions. Euroregions are the highest form of cross-border cooperation, and their structures are the most comprehensive and effective form of education, within which various cooperation, coordination and corporate mechanisms are formed and operate. The development and implementation of fundamentally new approaches to the development of euroregions in Ukraine in the context of EU enlargement require radical changes in the geopolitical situation on the European continent and a change in the geopolitical status of euroregions after a large-scale expansion of the european community.Summarizing the approaches to determining the essence of the euroregion the main functions of the latter are outlined: building strong cross-border links; addressing socio‐economic, political and environmental issues problems of border territories; improving the standard of living of the population of border territories; information functions; establishment of communication channels; participation in the establishment of personnel and migration policy, as well as in improving legislation on cross-border cooperation; creating a positive image of a stable, responsible partner in the international arena, etc.The expediency of an interactive level of international relations is noted, because at the present stage cross-border cooperation should be subject to a certain interactivity. In the context of this study, under interactivity refers to the exchange and addition of information and Human Resources Potential between by the parties of the euroregion, which should include the development of Joint Information, political, social‐economic projects. The key point is the information process and the process of communication between population of the Euroregion.
Keywords: euroregions, euroregional cooperation, cross-border cooperation, factors